2009
DOI: 10.1007/s11368-009-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of particulate organic carbon and dissolved organic carbon on removal of polycyclic aromatic hydrocarbons, organochlorine pesticides, and nonylphenols in a wetland

Abstract: Background, aim, and scope The potential of wetlands for controlling point-and nonpoint-source pollution in surface water has attracted increasing interest. The partitioning process of organic contaminants between water, particulate organic carbon (POC) and dissolved organic carbon (DOC), impacts their behaviors in the aquatic environments. Meantime, the partitioning process of organic contaminants is closely related to their physicochemical properties, such as hydrophobicity (or K ow ), and their fates in wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Previous studies showed that properties of organic amendments are an important factor in affecting pesticide sorption in amended soils (Dunigan and MacIntosh 1971;Dolaptsoglou et al 2007;Luo et al 2009). Biochar is also known as black carbon that is derived from biomass.…”
Section: Treatmentmentioning
confidence: 99%
“…Previous studies showed that properties of organic amendments are an important factor in affecting pesticide sorption in amended soils (Dunigan and MacIntosh 1971;Dolaptsoglou et al 2007;Luo et al 2009). Biochar is also known as black carbon that is derived from biomass.…”
Section: Treatmentmentioning
confidence: 99%
“…The organic matterrepresented by total organic carbon (TOC) and total nitrogen (TN)-buried in the sediments of aquatic systems, can induce the mobilization of iron and manganese and affect environmental quality (Baldock et al 2004;Luo et al 2009;Wu et al 2012;Neidhardt et al 2014). Labile organic carbon (LOC), such as glucose and cellulose, is known to alter sedimentary carbon dynamics by modifying the rate of mineralization of TOC (Guenet et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of EDCs and factors affecting their adsorption behaviors have been widely studied (e.g. Qiao et al 2008;Luo et al 2009;Cunha et al 2012;Kiran and Venkata 2012;Wang et al 2012). Dobor et al (2012) investigated the adsorption of selected acidic drugs by river sediments and found that the adsorption amount was positively correlated with the organic matter content (OM) and negatively correlated with pH.…”
Section: Introductionmentioning
confidence: 99%